Zelene površine kot dejavnik kvalitete okolja v Mariboru - Vovk Korže, Ana (Revija za geografijo, 2006)
In the article the type of green system and its function in Maribor is presented. There are many offical clasifications of green systems. The green system in the city has many functions. The aim of article is to show the situation of green system in the city and its protection. But the biodiversity in the city is not protected enough.
Keywords: ecology; ekologija; environmental protection; Maribor; mesta; varstvo okolja; zelene površine